2014
DOI: 10.2147/idr.s55376
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives on the spread of dengue in India

Abstract: Dengue fever (DF) and dengue hemorrhagic fever (DHF) are important arthropod-borne viral diseases. Each year, there are ~50 million dengue infections and ~500,000 individuals are hospitalized with DHF, mainly in Southeast Asia. Dengue in India has dramatically expanded over the last few decades, with rapidly changing epidemiology. The first major DHF outbreak in the entire nation occurred in 1996 by dengue virus serotype 2, and after a gap of almost a decade, the country faced yet another DF outbreak in the ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 26 publications
0
53
0
Order By: Relevance
“…After that, DENV-1 became predominant and one or more of these serotypes concomitantly circulate in the absence of cross immunity [10].…”
Section: Discussionmentioning
confidence: 99%
“…After that, DENV-1 became predominant and one or more of these serotypes concomitantly circulate in the absence of cross immunity [10].…”
Section: Discussionmentioning
confidence: 99%
“…The Indian subcontinent with its diverse climatic conditions and landscape is endemic for dengue and the region continues to experience outbreaks that vary in serotypic and spatial epidemiology (Raheel et al, 2011). Even though the occurrence of dengue fever in India was first documented during 1946, the first major dengue outbreak was reported during 1963-1964 from Kolkata, a dense urban city in Eastern India (Gupta and Ballani, 2014;Gupta et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…DENV-1 was the first isolated serotype in 1956 from Vellore, south India (Gupta et al, 2012), however, DENV-2 and DENV-3 were associated with several outbreaks across the country (Anoop et al, 2010;Gupta et al, 2006;Vinodkumar et al, 2013Vinodkumar et al, ) until 2008 when DENV-1 predominance was reported from Delhi in northern India (Chakravarti et al, 2010). More recent data report outbreaks of this disease with co-circulation of all four DENV serotypes in various parts of the country (Gupta and Ballani, 2014;Gupta et al, 2012). In southern India, reports from the states of Kerala, Telengana and southern parts of Tamil Nadu have genetically characterized circulating DENV strains isolated from outbreaks (Anoop et al, 2010;Dash et al, 2011;Paramasivan et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Dengue viruses can cause a wide variety of clinical illnesses ranging from mildly symptomatic dengue fever (DF) to more dangerous clinical conditions with capillary leakage syndrome such as dengue shock syndrome (DSS) and dengue hemorrhagic fever (DHF) (Gupta et al, 2014).…”
Section: Introductionmentioning
confidence: 99%